Object-Oriented Programming Applied to the Finite Element Method Part II. Application to Material Behaviors - Besson, Jacques; Leriche, Rodolphe; Foerch, Ronald; Cailletaud, Georges (European Journal of Computational Mechanics, 1998)
This paper examines the application of C++ design patterns to the development of material constitutives equations to be used infinite element simulation softwares. All material behaviors use the same generic inteiface. Accordingly, the same governing principles can be applied to simple elasto-(visco)-plastic materials as well as single crystals, polycrystals and multiphased materials. As these models use numerous parameters, a generic optimization tools was also developed to adjust these parameters. Finally, a specific pre-processor can be used to quickly implement and test new material behaviors. The result (i.e., inteiface +optimizer+ pre-processor) is an integrated approach to the development of new constitutive equations for structural computations.